AI Empowers Data Scientists to Become Strategic Leaders : From Technical Execution to Business Impact - Vineetha Sasikumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores how artificial intelligence catalyzes transforming the data scientist's role from technical practitioner to strategic business partner. By automating routine tasks such as data cleaning, feature engineering, and model selection, AI enables data scientists to redirect their expertise toward higher-value activities. The integration of advanced analytical capabilities—including natural language processing and computer vision—further enhances their ability to extract meaningful insights from complex datasets. Additionally, AI facilitates improved communication through automated reporting and explainable models, bridging the gap between technical findings and business applications. This strategic repositioning empowers data scientists to focus on critical responsibilities such as defining business problems, designing impactful experiments, and effectively communicating insights that drive organizational decision-making. Rather than replacing data scientists, AI augments their capabilities, allowing them to evolve from technical executors to strategic leaders who directly influence product strategy and business outcomes.
Keywords: Strategic Data Science; AI Automation; Explainable AI; Business Partnership; Analytical Transformation